CSA Country Profiles - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The CSA Country Profiles were originally developed in Latin America, then scaled out to Africa, Asia and Europe. Over 30 countries have CSA Profiles developed or in development.